Coping with mortality: responses of monkeys and great apes to collapsed, inanimate and dead conspecifics. Issue 1 (2nd January 2022) - De Marco, Arianna; Cozzolino, Roberto; Thierry, Bernard
Abstract : It was long assumed that only humans can distinguish the living from the dead. Renewed interest in this question over the last decade has led several authors to assert that non-human primates are also aware of death. We investigate this issue by comparing the behaviours of monkeys and great apes toward helpless conspecifics, basing our analysis on published reports. We first examine the behaviours of mothers towards the body of their dead offspring. They may carry the corpse for days or more before abandoning it. They groom, inspect and protect it, sometimes allowing group members to explore it, and rare cases of cannibalism have been reported. No significant difference is observed in the way that monkeys and great apes treat the bodies of infants. We then examine responses to collapsed (still able to move and react) and inanimate (unresponsive or dead) conspecifics. Monkeys and great apes guard, care for and inspect their helpless partners, and also manipulate and mobilise them. Through these actions, individuals may inform themselves about the state of their partners, test their responsiveness and/or attempt to rouse them. It appears that only chimpanzees and gorillas show violent action such as display behaviours and the rough treatment of bodies. They can also make distress calls, and periods of "stunned silence" sometimes occur in chimpanzees, indicating that they are experiencing intense emotion. Finally, we argue that while both monkeys and great apes detect body dysfunction through the victims' inability to wake up and move, only great apes can understand that something serious has happened. The signs of emotional disturbance reported in them indicate that they may believe that inanimate conspecifics have entered a state of "dormancy", meaning that they are unlikely to regain wakefulness. However, there is no evidence that any non-human primates are aware of mortality.